The International Conferences on Applied Science and Health (ICASH): Efforts and Commitments in Translating Research Results into Policy and Practices, for a Better Society - Widyastari, Dyah Anantalia; Sinaga, Doni Marisi; Wibowo, Canggih Puspo; Rahman, Pamuko Aditya; Noor, Hafizh Muhammad; Irawan, Dimas Sondang; Fatmarizka, Tiara; Diary, Dwina Gustia; Putra, I Gusti Ngurah Edi; Maretalinia, Maretalinia; Viniriani, Marina Ayu; Destiwi, Monita; Shidiq, Galih Albarra; Pratiwi, Ivana Aprilia; Kusuma, Made Dian Shanti; Dharmapatni, Ni Wayan Kesari; Pratama, Mahendrawan Nugraha Aji; Norsaputra, Ary; Pancanugraha, Andi; Kurniawan, Febrian Hendra; Putra, Wahyu Manggala; Fattah, Rifqi Abdul; Moehas, Puput Kusumawardani; Samosir, Ricky Alexander; Hananto, Andang Adi Fitria; Agastya, I Gusti Ngurah; Susilo, Taufik Eko; Vejvisithsakul, Pichpisith Pierre; Nauphar, Donny; Sari, Ariestya Indah Permata; Macnab, Andrew John (GHMJ (Global Health Management Journal), 2019)
-